2023
DOI: 10.1128/spectrum.04386-22
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus nsp5 Induces Incomplete Autophagy by Impairing the Interaction of STX17 and SNAP29

Abstract: A substantial number of viruses have been demonstrated to utilize or hijack autophagy to benefit their replication. In the case of porcine reproductive and respiratory syndrome virus (PRRSV), previous studies have demonstrated the proviral effects of autophagy on PRRSV proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that PRRSV induces autophagy to facilitate its proliferation ( 15 17 ). Later studies have further shown that PRRSV Nsps, including Nsp2, Nsp3, and Nsp5, play critical roles in the induction of autophagy ( 18 21 ). For example, PRRSV Nsp2 is determined to trigger autophagy through induction of endoplasmic reticulum stress or aggresome formation ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that PRRSV induces autophagy to facilitate its proliferation ( 15 17 ). Later studies have further shown that PRRSV Nsps, including Nsp2, Nsp3, and Nsp5, play critical roles in the induction of autophagy ( 18 21 ). For example, PRRSV Nsp2 is determined to trigger autophagy through induction of endoplasmic reticulum stress or aggresome formation ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%